Nursing professionals' knowledge of humanized care in a neonatal intensive care unit - Gomes, Maria Fernanda Pereira; Silva, Natália Santos da; Capellini, Verusca Kelly; Santos, Mariana Souza (Journal of Health Care, 2017)
Objective: To identify the knowledge of nursing professionals working in a neonatal intensive care unit (Nicu) of the humanized care for newborns. Method: This is a quantitative and descriptive study, carried out in a Nicu of a hospital in the state of São Paulo, Brazil. The study subjects were 24 nursing professionÂals, including 6 nurses, 5 nurse technicians and 13 assistants. Data were collected through a questionnaire prepared from the theoretical framework of the Ministry of Health on Humanization. Results: UnanÂimously nursing professionals regard as humanized care the use of techniques that mitigate pain when performing painful procedures. Other characteristics indicated by most of the professionals interviewed were to sanitize and warm their hands when touching the baby and to minimize sounds and noises to improve comfort. Yet, the less identified characteristics were allowing all family members to touch the baby and resoluteness. Conclusion: The nurses understand humanized care as an important practice to be held every day with the newborn and his or her family, however, few answered that they know about the powers and duties that they should have regarding the newborn care and the level of resoluteness that is an important part of humanized care.
Keywords: Humanization of assistance; Intensive care units; Neonatal; Nursing care